Intracranial hypotension syndrome in chronic subdural hematomas - Cabieses Molina, Fernando (1951)
The logical relationship between the presence of intracranial expansive lesions and symptoms resulting from intracranial hypertension suffers an occasional jolt when the presence of an intracranial hypotension in some individuals with a chronic subdural hematoma is found.